HOW TO INSULT AND COMPLIMENT A TESTIFIER. (10th November 2016) - Malcolm, Finlay
ABSTRACT: Do we insult or slight a speaker when we reject her testimony? Do we compliment or commend her when we accept her testimony? This paper argues that the answer to both of these questions is "yes", but only in some instances, since these respective insults and compliments track the reasons a hearer has for rejecting or accepting testimony. When disbelieving a speaker, a hearer may insult her because she judges the speaker to be either incompetent as a knower or insincere as a teller. By outlining the predominant reasons we have for rejecting testimony, I show how not every instance of rejecting testimony embodies this negative evaluation of the speaker. By contrast, testimonial compliments are fewer in number, and are not constitutive of "everyday" testimonial exchanges, since speakers who are competent as knowers and sincere as tellers are merely behaving correctly in accordance with the norms of testifying. Nevertheless, deferring to an authority on belief can be complimentary to that speaker if by doing so we judge her to have some mastery in a particular domain. This suggests an asymmetry between rejecting and accepting testimony. Testimonial insults and compliments also have important moral applications, particularly regarding epistemic injustice and therapeutic trust.